PERANCANGAN DESAIN USER INTERFACE APLIKASI MOBILE “TINTROPIC” SEBAGAI PANDUAN PERSONAL COLOR DAN PEMILIHAN WARNA KOSMETIK - Kristiwi, Kandiya Asoka; Nirwana, Aditya; Prasetya, Bintang Pramudya Putra (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
Selecting appropriate makeup colors and shades that complement natural features such as skin tone, eye color, and hair color often poses a significant challenge for cosmetic users. One approach to assist in determining suitable colors is Personal Color Analysis (PCA), a method used to identify a personalized color palette. However, PCA services typically require consultation with specialists and remain inaccessible to many due to location and cost constraints. This study focuses on the user interface (UI) design of a mobile-based PCA service, aiming to provide an alternative means for conducting personal color tests and delivering analysis results in the form of customized color palettes and recommendations for locally available cosmetic products. The design process employed the design thinking methodology, and the effectiveness of the interface was evaluated through user testing. Results indicated that the overall UI design successfully conveyed the application’s core functions, although instances of misclicks were observed on certain pages.